Tuning of natural frequency with electromagnetic shunt mass. (21st January 2019) - Zheng, Wenguang; Yan, Bo; Ma, Hongye; Wang, Rongyang; Jia, Jiangming; Zhang, Lu; Wu, Chuanyu
Abstract: In previous studies, the negative impedance electromagnetic shunt damping (EMSD) can increase the damping of host structures to reduce the unexpected vibration. This paper proposes a novel electromagnetic shunt mass (EMSM) concept, which can tune the natural frequency of an electro-mechanical system and simultaneously suppress vibration. The EMSM means that the mass of a system can be controlled with the EMSD. An electromagnetic transducer is designed and modeled. The negative inductance negative resistance (NINR) and the positive inductance negative resistance (PINR) shunts are proposed to investigate the tuning of the natural frequency characteristics. The governing equation of the coupling system is derived, and the EMSM model is established in frequency domain. The optimal resistance and inductance of the shunt are analyzed theoretically, and the root locus is employed to judge the stability of the coupling system. The laboratory experiment was setup to verify the EMSM concept. The results demonstrate that the EMSM can electrically tune the natural frequency of the electromagnetic transducer. Furthermore, the NINR–EMSM has the excellent performance in isolation region, and the PINR–EMSM is more effective to suppress the low frequency vibrations in resonant region.